Social Identity and Depression Among the Elderly: Evidence from India - Punarjit Roychowdhury (Global Labor Organization (GLO), 2024)
The paper examines the prevalence of depression and clinical depression among the elderly in India across groups with distinct social identities, where social identities are defined by caste and religious affiliations. Using nationally representative data, the study reveals no- table disparities. Compared to upper caste-Hindus (UC-Hindus), disadvantaged groups like Scheduled Castes (SCs), Scheduled Tribes (STs), and Other Backward Classes (OBCs) expe- rience more depression. Further, SCs and OBCs are also more likely to be clinically depressed than UC-Hindus; however, there is no significant difference in clinical depression likelihood between UC-Hindus and STs. The gaps in depression and clinical depression across social groups diminish when I control for socioeconomic status and disappear with further adjust- ments for life conditions and experiences, including childhood circumstances, experiences of discrimination, neighborhood characteristics, housing conditions and perceived deprivation. Surprisingly, after accounting for these factors, STs demonstrate the lowest likelihood of clinical depression among all groups. While this could be interpreted as suggesting that STs inherently have better mental health than others, a more plausible explanation is that they under-report the symptoms used in clinical depression diagnosis.
Keywords: I14; I15; I31; J14; O12; 330; Depression; India; Mental Health; Social Identity